2014
DOI: 10.13005/msri/110204
|View full text |Cite
|
Sign up to set email alerts
|

Review on Machining of Aluminium Metal Matrix Composites

Abstract: Metal matrix composites have superior mechanical properties in comparison to metals over a wide range of operating conditions. This make them an attractive option in replacing metals for various engineering applications. This paper provides a literature review, on machining of Aluminium metal matrix composites (AMMC)especially the particle reinforced Aluminium metal matrix composites. This paper is an attempt to give brief account of recent work to predict cutting parameters &surface generated in AMMC.By s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…This reason has resulted in various research into the machinability studies of AMCs. Research has shown that the presence of the hard-reinforcing particles incorporated into the aluminium alloy matrix while improving the properties of the composite, increases the difficulty in machining the said composites [11,12]. Such difficulties include increased surface roughness, increased tool wear, and increased cutting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This reason has resulted in various research into the machinability studies of AMCs. Research has shown that the presence of the hard-reinforcing particles incorporated into the aluminium alloy matrix while improving the properties of the composite, increases the difficulty in machining the said composites [11,12]. Such difficulties include increased surface roughness, increased tool wear, and increased cutting temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics include: hardness, corrosion resistance, wear resistance and thermal resistance. Thanks to their greater hardness than that of the matrix material, aluminium composites are regarded to be more difficult to machine than the matrix alone because of the blade wear index [1][2][3]. Another major index of material machinability is the cutting force.…”
Section: Introductionmentioning
confidence: 99%
“…Shape of the reinforcement may be fiber, particulate or whiskers type; fiber and particulates are most commonly used shape of the reinforcement. A proper selection of matrix & reinforcement and shape of the reinforcement is highly desirable for property improvement of the composite [7][8][9]. In recent years, aluminium and its alloys are most widely used non-ferrous metals and getting more popularity due to its high strength to weight ratio, easy to fabricate, and low production cost [10,11,12].…”
Section: Introductionmentioning
confidence: 99%